Further Insight into the Effectiveness of a Behavioral Teacher Program Targeting ADHD Symptoms Using Actigraphy, Classroom Observations and Peer Ratings - Veenman, Betty; Luman, Marjolein; Oosterlaan, Jaap (Frontiers in Psychology, 2017)
Objective: The Positivity & Rules program (PR program), a low-level behavioral teacher program targeting symptoms of attention-deficit/hyperactivity disorder (ADHD), has shown positive effects on teacher-rated ADHD symptoms and social functioning. This study aimed to assess whether program effects could be confirmed by instruments assessing classroom behavior other than teacher-ratings, given teachers’ involvement with the training. Methods: Participants were 114 primary school children (age = 6-13) displaying ADHD symptoms in the classroom, who were randomly assigned to the treatment (n = 58) or control group (n = 65). ADHD symptoms were measured using classroom observations and actigraphy, and peer acceptance was measured using peer ratings. Intention-to-treat multilevel analyses were conducted to assess program effects. Results: No beneficial program effects were found for any of the measures. Conclusion: The earlier beneficial program effects on both ADHD symptoms and social functioning reported by teachers, may be explained by a change in the perception of teachers rather than changes in the child’s behavior. Other methodological explanations are also discussed, such differences between instruments in the sensitivity to program-related changes. The current study underlines the importance of using different measures of classroom behavior to study program effects.